'Flash houses': Public houses and geographies of moral contagion in 19th-century London. (February 2022) - Bland, Eleanor
'Flash houses', a distinctive type of public house associated with criminal activity, are a shadowy and little-studied aspect of early 19th-century London. This article situates flash houses within a wide perspective, arguing that the discourses on flash houses were part of concerns about the threat of the urban environment to the moral character of its inhabitants. The article draws on an original synthesis of a range of sources that refer to flash houses, including contemporary literature, newspapers, court documents, and government papers. It demonstrates that flash houses were part of both popular intrigue about the perceived 'criminal underworld' and official concerns about the collusion between police officers and suspected offenders, since police officers allegedly frequented flash houses to gather criminal information. A detailed examination of this term reveals anxieties about the state of the metropolis, poverty, and criminality that were central to the early 19th-century consciousness. However, the discussion of flash houses in this context also demonstrates a powerful connection in contemporary minds between the physical spaces of the city and the risks that they posed to inhabitants' morals. While associations between the physical environment and morality have been drawn throughout history, flash houses represent a paradigmatic moment in this dialogue. This is because different moral concerns coalesced around the discourse on flash houses: anxieties about the criminal underworld, the potential for moral degradation of young people who frequented these spaces, and the corruption of police officers through contact with known or suspected offenders.